Sosialisasi Pencegahan Bullying Siswa Sekolah Dasar dan Sekolah Menengah Pertama di Desa Netampin Kabupaten Barito Timur - Joshua Evan Savero; Eka Pebriyanti; Eva Apriliana; Rahmat; Muhammad Amir Jailani; Ratna Pancawati (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Bullying that occurs in Indonesia is often found in school environments, both formal and non-formal. Bullying cases often occur around 61-73% in the form of violence, blackmail, threats and taking things, the rest are cases of bullying in other forms such as cyberbullying. With support from the Government, there is no need to hesitate to pay attention to and even respond to bullying behavior. Therefore, students from the Regular Real Work Lecture (KKN) Period II at Palangka Raya University were given the opportunity to provide counseling or outreach related to efforts to prevent bullying behavior among students in Netampin Village, Dusun Tengah District, East Barito Regency. Preventing bullying can be done by empowering children to be able to detect, fight back and provide support when bullying occurs. Schools can also take preventive steps, such as building effective communication between teachers and students, holding discussions and lectures about bullying behavior, creating a safe school environment, and providing support for victims of bullying